Aspects of Socio-Economic Success in a Labrador Village - Southard, Frank E. (Culture, 1981)
During the last generation, the people of southern Labrador have enjoyed increasing contact with a number of sources of external information and, consequently, have developed middle class Canadian and American consumer desires. The degree to which these desires can be satisfied only partially determines the status of families in the community studied. This paper concerns how the community limits the definition of “success”. First, I briefly sketch the history and development of the community since its settlement to show the nature of traditional and modern values. Then the current community concept of “success” is examined with respect to its material and social constraints.